Global mean potassium intake: a systematic review and Bayesian meta-analysis. - Reddin, Catriona; Ferguson, John; Murphy, Robert; Clarke, Aoibhin; Judge, Conor; Griffith, Vincent; Alvarez, Alberto; Smyth, Andrew; Mente, Andrew; Yusuf, Salim; O'Donnell, Martin J. (European Journal of Nutrition, 2023)
Purpose: Increasing potassium intake, especially in populations with low potassium intake and high sodium intake, has emerged as an important population-level intervention to reduce cardiovascular events. Current guideline recommendations, such as those made by the World Health Organisation, recommend a potassium intake of > 3.5 g/day. We sought to determine summary estimates for mean potassium intake and sodium/potassium (Na/K) ratio in different regions of the world. Methods: We performed a systematic review and meta-analysis. We identified 104 studies, that included 98 nationally representative surveys and 6 multi-national studies. To account for missingness and incomparability of data, a Bayesian hierarchical imputation model was applied to estimating summary estimates of mean dietary potassium intake (primary outcome) and sodium/potassium ratio. Results: Overall, 104 studies from 52 countries were included (n = 1,640,664). Mean global potassium intake was 2.25 g/day (57 mmol/day) (95% credible interval (CI) 2.05–2.44 g/day), with highest intakes in Eastern and Western Europe (mean intake 3.53g/day, 95% CI 3.05–4.01 g/day and 3.29 g/day, 95% CI 3.13–3.47 g/day, respectively) and lowest intakes in East Asia (mean intake 1.89 g/day; 95% CI 1.55–2.25 g/day). Approximately 31% (95% CI, 30–41%) of global population included have an estimated potassium intake > 2.5 g/day, with 14% (95% CI 11–17%) above 3.5 g/day. Conclusion: Global mean potassium intake (2.25 g/day) falls below current guideline recommended intake level of > 3.5 g/day, with only 14% (95% CI 11–17%) of the global population achieving guideline-target mean intake. There was considerable regional variation, with lowest mean potassium intake reported in Asia, and highest intake in Eastern and Western Europe.